2012
DOI: 10.1155/2012/202515
|View full text |Cite
|
Sign up to set email alerts
|

Histology and Mucous Histochemistry of the Integument and Body Wall of a Marine Polychaete Worm,Ophryotrochan. sp. (Annelida: Dorvilleidae) Associated with Steelhead Trout Cage Sites on the South Coast of Newfoundland

Abstract: Histology and mucous histochemistry of the integument and body wall of a marine polychaete worm,Ophryotrochan. sp. (Annelida: Dorvilleidae) associated with Steelhead trout cage sites on the south coast of Newfoundland. A new species of polychaete (Ophryotrochan. sp. (Annelida: Dorvilleidae)) was identified from sediment below Steelhead trout cages on the south coast of Newfoundland, Canada. The organisms were observed to produce a network of mucus in which groups of individuals would reside. Questions regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Species belonging to the genus Ophryotrocha can be found in organically enriched soft sediments (Dahlgren et al 2001), but the highest densities have been found in the deep sea on whale-falls (Dahlgren et al 2006, Wiklund et al 2009a,b, 2012, Salvo et al 2014 and hard substrates underneath fish farms in Norway and Canada (Murray et al 2012, Eikje 2013, Salvo et al 2014. Ophryotrocha spp.…”
Section: Introductionmentioning
confidence: 99%
“…Species belonging to the genus Ophryotrocha can be found in organically enriched soft sediments (Dahlgren et al 2001), but the highest densities have been found in the deep sea on whale-falls (Dahlgren et al 2006, Wiklund et al 2009a,b, 2012, Salvo et al 2014 and hard substrates underneath fish farms in Norway and Canada (Murray et al 2012, Eikje 2013, Salvo et al 2014. Ophryotrocha spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, opportunistic annelid complexes (termed OPC) were observed on rocky substrates underneath finfish aquaculture cages on the south coast of Newfoundland, and were linked to fish farm activity (Murray et al 2012;Hamoutene et al 2013). OPC are visible during video surveys of the seafloor: they typically form dense colonies surrounded by mucus that can completely obstruct the view of the substrate (Hamoutene et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Annelids forming OPC in Newfoundland were identified as belonging to the genus Ophryotrocha Claparède & Mecznikow, 1869, family Dorvilleidae (Murray et al 2012). Dorvilleids live in a range of habitats from shallow water (Hilbig & Blake 1991;Prevedelli et al 2005) to the deep sea, including extreme habitats such as methane seeps (Levin & Michener 2002;Levin et al 2006;Decker & Olu 2010;Thurber et al 2010), hydrothermal vents (Blake & Hilbig 1990;Weiss & Hilbig 1992;Bergquist et al 2007;Paxton & Morineaux 2009), aquaculture sites FIGURE 4.…”
Section: Introductionmentioning
confidence: 99%
“…Ophryotrocha species are also associated with organically enriched sediments (Dahlgren et al 2001). They are, however, mainly found in the deep sea on whale-falls (Dahlgren et al 2006, Wiklund et al 2009a) and on hard substrates underneath fish farms in Norway and Canada (Murray et al 2012, Salvo et al 2014. In this thesis we show that both polychaete species feed and grow on salmon faeces, and we highlight their potential as extractive species to be included in IMTA (Chapter 4 & 5).…”
Section: Open-water Imtamentioning
confidence: 73%
“…as extractive species for IMTA systems. Species belonging to the genus Ophryotrocha can be found in organically enriched soft sediments (Dahlgren et al 2001), but the highest densities have been found in the deep sea on whale-falls (Dahlgren et al 2006, Wiklund et al 2009a,b, Wiklund et al 2012, Salvo et al 2014) and hard substrates underneath fish farms in Norway and Canada (Murray et al 2012, Eikje 2013, Salvo et al 2014. Ophryotrocha spp.…”
Section: Introductionmentioning
confidence: 99%